Information Technology in Marketing: Implications in Marketing of Equality Education Programs - Sutrisno Sutrisno; Galih Wisnu Wardhana; Abdul Kadir; Froilan Delute Mobo (Journal of Nonformal Education, 2025)
Beground -  The equality education program in Banjarmasin has an important role in providing learning opportunities for people who cannot access formal education. However, challenges in terms of marketing this program are still an obstacle, such as the lack of public understanding of the benefits of equality education and limitations in reaching prospective students. Along with the development of information technology, the implementation of digital-based marketing strategies is a potential solution to increase the reach and effectiveness of the promotion of this program. Purpose - This study aims to explore the implications of the use of information technology in the marketing of equality education programs in Banjarmasin.               Method/approach - The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and document analysis. The research informants consisted of the manager of the Center for Community Learning Activities (PKBM), educators, and students involved in the equality program. Findings - Research findings show that the use of information technology, such as social media, websites, and mobile-based applications, has had a positive impact on increasing the visibility of equality education programs. The use of digital platforms allows for a wider reach, increased interaction with prospective students, and more effective and efficient delivery of information. However, challenges such as limited internet access in some regions and the lack of digital literacy among the community are still obstacles that need to be overcome. Conclusions - The conclusion of this study confirms that the application of information technology in the marketing of equality education programs in Banjarmasin can increase community participation and the effectiveness of information delivery. A more targeted and sustainable digital marketing strategy is needed to overcome existing obstacles. Novelty/Originality/Value - The novelty of this study lies in the development of an information technology-based marketing model that is tailored to the demographic and social characteristics of the Banjarmasin community, so that it can be a reference for equality education program managers in increasing public participation and awareness of the importance of non-formal education.